The primary-to-secondary school transition for children on the autism spectrum: A multi-informant mixed-methods study. (January 2017) - Makin, Chantelle; Hill, Vivian; Pellicano, Elizabeth
Background and aims: Children diagnosed with an autism spectrum condition are known anecdotally to be especially vulnerable during the transition to secondary school. Yet, very little is known about the child-, school- and system-level factors that can potentially make changing schools particularly difficult for these children. Here, we report on a mixed-method study, which examined the factors that influence a successful school transition for autistic children in one local education authority in England. Methods: Fifteen children were seen twice in the space of four months – once during the final term of their mainstream primary school and again during the first term of secondary school. Parents and teachers were also interviewed at both time points. Results: Overall, our participants reported negative experiences of their transition to secondary school – regardless of the type of secondary provision (mainstream or specialist) to which they transferred. None of the child-level factors measured during the pre-transition phase, including verbal ability, autistic symptomatology, sensory responsiveness and anxiety, predicted children's transition success four months later. Rather, transition success appeared to be predominantly related to several school- and system-level factors, including tensions over school choice, delays in placement decisions, lack of primary preparation and communication between schools. Identity-related issues were also a key concern for many children, which appeared to have a particularly negative influence on adjustment to their new school. Conclusions: We identified predominantly negative experiences of primary-to-secondary transition for the autistic children sampled here, which appeared to be accounted for largely by school- and system-level factors. Implications: Applying interventions that are designed to ease the transition to secondary school by modifying the school environment before, during and after transition to improve the fit between the autistic child and their educational environment should go some way in tackling school-related barriers to a successful transition for these children. System-level changes in the way that local authorities manage the transition process may also improve children and families' experiences.